Preparation method of Li2ZrO3ZrO2 co-coated positive electrode material and solid battery

Through the preparation method of Li2ZrO3&ZrO2 co-coated positive electrode material, the problem of poor stability of solid-state battery positive electrode materials in sulfide solid electrolytes is solved, and higher stability and lower preparation costs are achieved.

CN119447210APending Publication Date: 2025-02-14PETROCHINA SHENZHEN NEW ENERGY RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310985833.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The problem of poor stability of solid-state battery positive electrode materials in sulfide solid electrolytes and difficulty in mass production.

Method used

The preparation method of Li2ZrO3&ZrO2 co-coated positive electrode material is adopted, and an effective cladding layer is formed through ball milling and high-temperature annealing steps to improve the interface stability between the positive electrode material and the sulfide electrolyte.

Benefits of technology

It improves the stability and life of the positive electrode material of solid-state battery, reduces the preparation cost, and provides technical support for the mass production of positive electrode materials of solid-state battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447210A_ABST
    Figure CN119447210A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid battery positive electrode material manufacturing, in particular to Li2ZrO3amp. The invention discloses a preparation method of a ZrO2 co-coated positive electrode material and a solid battery. The method comprises the following steps: carrying out first ball milling on ZrO2 nanoparticles and a high-nickel positive electrode material according to a mass ratio of 0.1: 100-10: 100 to obtain a mixed material I; adding Li2ZrO3 with the same molar weight as the ZrO2 nanoparticles into the mixed material I, and carrying out secondary ball milling to obtain a mixed material II; the mixed material II is subjected to high-temperature annealing, and Li2ZrO3amp is obtained; the positive electrode material is co-coated with ZrO2. According to the invention, optimization is carried out aiming at the problem of poor stability of an existing positive electrode material in an all-solid-state battery, and Li2ZrO3amp is used; the positive electrode material is coated with ZrO2, so that the stability problem between the positive electrode material and a sulfide electrolyte interface is improved, meanwhile, the coating process is optimized, the preparation cost of the positive electrode material is reduced, and technical support is provided for batch preparation of solid battery positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid batteries, and in particular to a preparation method of a Li2ZrO3&ZrO2 co-coated positive electrode material and a solid battery. Background Art

[0002] At present, solid-state batteries have attracted more and more attention due to their high safety and high specific energy prospects. However, the positive electrode of solid-state batteries faces problems such as poor physical contact, chemical side reactions, and slow ion / electron transfer. At present, a variety of high-ion conductivity solid-state electrolytes have been successfully developed, including garnet-type electrolytes LLZO, perovskite-type electrolytes, and LGPS. Oxide solid-state batteries have high mechanical strength and require high-temperature quenching to achieve effective contact between the electrolyte and the positive electrode material, but this will cause irreversible capacity decay of the positive electrode material at the electrolyte / electrolyte interface. Sulfide electrolytes are soft in texture and have good interface contact with the positive electrode material.

[0003] Although sulfide all-solid-state batteries have many advantages, there are still some technical bottlenecks that need to be solved, such as the interface problem between high-nickel cathode materials and sulfide solid electrolytes. High-nickel materials are currently the highest energy density cathode materials commercially available, with the advantages of high gram capacity and voltage platform, but there is a space charge layer between high-nickel materials and sulfide solid electrolytes, which causes the cathode material to decay, so an interface layer is needed to improve the life of the cathode material.

[0004] Surface coating is a commonly used method to enhance the life of positive electrode materials. It can enhance the interface stability between positive electrode materials and sulfide electrolytes. The main coating methods are LiNbO3, Li2ZrO3, LiAlO2, Li3B 11 O 18 , ZrO2, Al2O3, etc. Among them, ZrO2 coating is considered to be a relatively effective and low-cost method. However, although ZrO2 can improve the interface stability, ZrO2 has electronic insulation and ion insulation, so it cannot effectively improve the stability of the positive electrode material in the solid-state battery. In contrast, Li2ZrO3 has better ion conductivity, which means that the Li2ZrO3 coating layer or ZrO2&Li2ZrO3 co-coating layer can effectively improve the life of the positive electrode material and can be used as a coating layer for the positive electrode material of the solid-state battery.

[0005] At present, the main coating methods are wet coating, ALD (atomic layer deposition), spray coating, etc., but each has its own defects. The wet coating process requires an additional drying process, and the economic and time costs in the production process are relatively high. The precursors used in ALD are generally toxic. The cost of spray coating machines is relatively high.

[0006] Therefore, it is necessary to develop an economical and simple method for preparing positive electrode coating to achieve the goal of mass production of solid-state battery positive electrode materials. Summary of the invention

[0007] The present application provides a preparation method of a Li2ZrO3&ZrO2 co-coated positive electrode material and a solid battery to solve the technical problems of poor stability and difficulty in mass production of existing solid-state batteries and sulfide solid electrolytes. In a first aspect, the present application provides a method for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material, the preparation method comprising the following steps: The ZrO2 nanoparticles and the high nickel cathode material are first ball-milled in a mass ratio of 0.1:100 to 10:100 to obtain a mixed material I; Adding Li2ZrO3 in the same molar amount as that of ZrO2 nanoparticles to the mixed material I, and performing a second ball milling to obtain a mixed material II; The mixed material II is subjected to high temperature annealing to obtain a Li2ZrO3&ZrO2 co-coated positive electrode material.

[0008] Optionally, the first ball milling process specifically includes: first ball milling at 500 rpm for 1 min, followed by ball milling at 2000 rpm for 6 min; the grinding process specifically includes: first ball milling at 500 rpm for 1 min, followed by ball milling at 2000 rpm for 6 min.

[0009] Optionally, the particle size of the ZrO2 nanoparticles is in the range of 2-100 nm, the particle size of the high-nickel positive electrode material is in the range of 100-5000 um; the mass ratio of the ZrO2 nanoparticles to the high-nickel positive electrode material is in the range of 1:100-5:100; The high nickel positive electrode material is selected from any one of NCM523, NCM622, NCM811, Ni90 and NCA.

[0010] Further optionally, the particle size range of the ZrO2 nanoparticles is 5-15nm, and the particle size of the high-nickel positive electrode material is 300-500um.

[0011] Optionally, the high temperature annealing of the mixed material II specifically includes: using an annealing temperature of 150-600° C. for a time of 1-24 hours.

[0012] Further optionally, the high temperature annealing of the mixed material II specifically includes: using an annealing temperature of 200-400° C. for 2-4 hours.

[0013] In a second aspect, the present invention provides a method for preparing a solid positive electrode material battery, comprising the following steps: The Li2ZrO3&ZrO2 co-coated positive electrode material prepared by the preparation method provided in the first aspect and the sulfide solid electrolyte LPSCl are mixed and ground evenly to obtain a composite positive electrode material; The LPSCl sulfide electrolyte is pressed into an electrolyte sheet, and then the obtained composite positive electrode material is added to one side of the electrolyte sheet, pressed into a sheet, and carbon paper is added as a current collector to obtain a composite positive electrode sheet; A Li-In alloy is added to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly and pressing to obtain a positive electrode material.

[0014] Optionally, when the Li2ZrO3&ZrO2 co-coated positive electrode material and the sulfide solid electrolyte LPSCl are mixed and ground, the mass ratio is 7:3; the mass ratio of the composite positive electrode material to the electrolyte sheet is 1:10.

[0015] Optionally, the LPSCl sulfide electrolyte is pressed into an electrolyte sheet, specifically comprising: 100 mg of the LPSCl sulfide electrolyte is pressed at 380 MPa for 1 min to form a sheet; The obtained composite positive electrode material is added to one side of the electrolyte sheet and pressed into a sheet, specifically comprising: taking 10 mg of the composite positive electrode material and adding it to one side of the electrolyte sheet, and pressing it at a pressure of 400 MPa for 10 minutes; Adding Li-In alloy to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly and pressing, specifically comprising: adding Li-In alloy to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly and pressing at a pressure of 50 MPa for 30 seconds.

[0016] In a third aspect, the present invention provides a solid battery, comprising a positive electrode and a negative electrode, wherein the positive electrode comprises a Li2ZrO3&ZrO2 co-coated positive electrode material prepared by the preparation method described in the first aspect.

[0017] The above technical solution provided by the present invention has the following advantages compared with the prior art: The present invention provides a preparation method of a Li2ZrO3&ZrO2 co-coated positive electrode material and a solid battery, which optimizes the poor stability problem of the current positive electrode material in an all-solid-state battery. The positive electrode material is coated with Li2ZrO3&ZrO2, which improves the stability problem between the positive electrode material and the sulfide electrolyte interface. At the same time, the coating process is optimized, the preparation cost of the positive electrode material is reduced, and technical support is provided for the batch preparation of positive electrode materials for solid batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0020] Figure 1 A schematic diagram of a process for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material provided in an embodiment of the present application; Figure 2 A schematic flow chart of a method for preparing a solid battery positive electrode material provided in Example 1 of the present application. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0022] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0023] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items (individuals) or plural items (individuals). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.

[0024] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0025] In the first aspect, the present application provides a method for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material, see Figure 1 , the method comprising: S1, ZrO2 nanoparticles and high nickel positive electrode materials are added into a high energy ball mill in a mass ratio of 0.1:100-10:100 for the first ball milling to obtain a mixed material I; In some embodiments, ball milling is performed at 500 rpm for 1 min, followed by ball milling at 2000 rpm for 6 min; the particle size range of the selected ZrO2 nanoparticles is 2-100 nm, and the particle size range of the selected high-nickel positive electrode material is 100-5000 um; the high-nickel positive electrode material can be any one of NCM523, NCM622, NCM811, Ni90 and NCA. In this embodiment, NCM622 is selected as the high-nickel positive electrode material.

[0026] In a more preferred embodiment, the particle size of the ZrO2 nanoparticles is in the range of 5-15 nm, and the particle size of the high nickel positive electrode material is in the range of 300-500 um.

[0027] In a preferred embodiment, the mass ratio of ZrO2 nanoparticles to high nickel positive electrode material is in the range of 1:100-5:100.

[0028] S2, adding Li2ZrO3 with the same molar mass as that of ZrO2 nanoparticles to the mixed material I, and performing a second ball milling to obtain a mixed material II; In some embodiments, the second ball milling is performed by first ball milling at 500 rpm for 1 min, followed by ball milling at 2000 rpm for 6 min.

[0029] S3, annealing the mixed material II at high temperature to make the high nickel positive electrode material and the Li2ZrO3&ZrO2 coating layer in closer contact, thereby obtaining a Li2ZrO3&ZrO2 co-coated positive electrode material.

[0030] In some embodiments, the high temperature annealing is performed at a temperature in the range of 150-600° C. and a time in the range of 1-24 h.

[0031] In a more preferred embodiment of the present invention, the temperature range of the high temperature annealing is 200-400° C., and the annealing time is 2-4 hours.

[0032] In a second aspect, this embodiment provides a method for preparing a positive electrode material of a solid battery, comprising the following steps: The Li2ZrO3&ZrO2 co-coated positive electrode material prepared in the first aspect and the sulfide solid electrolyte LPSCl are ground in a mass ratio of 7:3 to make them uniformly mixed to obtain a composite positive electrode material; Other high-nickel positive electrode materials can also be used to make co-coated positive electrode materials to participate in the subsequent production process; 100 mg of LPSCl sulfide electrolyte was weighed and pressed at a pressure of 380 MPa for 1 min to form an electrolyte sheet, and then 10 mg of the obtained composite positive electrode material was added to one side of the electrolyte sheet, and pressed at a pressure of 400 MPa for 10 min to form a sheet, and carbon paper was removed and added as a current collector to obtain a composite positive electrode sheet; Li-In alloy was added to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly, and then pressed at 50 MPa for 30 seconds to obtain the positive electrode material of the solid battery.

[0033] The Li2ZrO3&ZrO2 co-coated positive electrode material and the positive electrode material of the solid battery are both realized based on the above-mentioned preparation method. The specific steps of the preparation method can refer to the above-mentioned embodiment. Since the Li2ZrO3&ZrO2 co-coated positive electrode material and the positive electrode material of the solid battery adopt part or all of the technical solutions of the above-mentioned embodiments, they at least have all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.

[0034] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0035] Example 1 This embodiment provides a method for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material, comprising the following steps: The ZrO2 nanoparticles with a particle size of 100 nm and the high nickel cathode material NCM811 with a particle size of 5000 um were ball-milled for the first time at a mass ratio of 0.1:100, first at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material I; Add Li2ZrO3 in the same molar amount as that of ZrO2 nanoparticles to the mixed material I, and perform a second ball milling, first at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material II; The mixed material II was subjected to high temperature annealing at 150°C for 10 h to obtain Li2ZrO3&ZrO2@NCM811 co-coated positive electrode material.

[0036] Example 2 This embodiment provides a method for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material, comprising the following steps: The ZrO2 nanoparticles with a particle size of 15 nm and the high nickel cathode material Ni90 with a particle size of 100 um were ball-milled for the first time at a mass ratio of 5:100, first at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material I; Add Li2ZrO3 in the same molar amount as that of ZrO2 nanoparticles to the mixed material I, and perform a second ball milling, first at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material II; The mixed material II was subjected to high temperature annealing at 400°C for 2 h to obtain Li2ZrO3&ZrO2@Ni90 co-coated positive electrode material.

[0037] Example 3 This embodiment provides a method for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material, comprising the following steps: The ZrO2 nanoparticles with a particle size range of 5 nm and the high nickel cathode material NCM523 with a particle size of 300 um were selected for the first ball milling at a mass ratio of 10:100, firstly at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material I; Add Li2ZrO3 in the same molar amount as that of ZrO2 nanoparticles to the mixed material I, and perform a second ball milling, first at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material II; The mixed material II was subjected to high temperature annealing at 200°C for 4 hours to obtain Li2ZrO3&ZrO2@NCM523 co-coated positive electrode material.

[0038] Example 4 This embodiment provides a method for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material, comprising the following steps: The ZrO2 nanoparticles with a particle size range of 10 nm and the high nickel positive electrode material NCA with a particle size of 400 um were selected for the first ball milling at a mass ratio of 1:100, firstly at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material I; Add Li2ZrO3 in the same molar amount as that of ZrO2 nanoparticles to the mixed material I, and perform a second ball milling, first at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material II; The mixed material II was subjected to high temperature annealing at 300°C for 3 h to obtain Li2ZrO3&ZrO2@NCA co-coated positive electrode material.

[0039] Example 5 This embodiment provides a method for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material, comprising the following steps: The ZrO2 nanoparticles with a particle size range of 15 nm and the high nickel cathode material NCM622 with a particle size of 400 um were selected for the first ball milling at a mass ratio of 3:100, firstly at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain a mixed material I; Add Li2ZrO3 in the same molar amount as that of ZrO2 nanoparticles to the mixed material I, and perform a second ball milling, first at 500 rpm for 1 min, and then at 2000 rpm for 6 min, to obtain mixed material II; The mixed material II was subjected to high temperature annealing at 600°C for 1 h to obtain Li2ZrO3&ZrO2@NCM622 co-coated positive electrode material.

[0040] The material has a capacity of 130 mAh / g before coating and can be cycled for 50 times; the material has a capacity of 150 mAh / g after coating and can be cycled for 300 times.

[0041] Example 6 This embodiment provides a method for preparing a positive electrode material of a solid battery, comprising the following steps: The Li2ZrO3&ZrO2@NCM811 co-coated positive electrode material and the sulfide solid electrolyte LPSCl prepared in Example 1 were ground in a mass ratio of 7:3 to make them uniformly mixed to obtain a composite positive electrode material; 100 mg of LPSCl sulfide electrolyte was weighed and pressed at a pressure of 380 MPa for 1 min to form an electrolyte sheet, and then 10 mg of the obtained composite positive electrode material was added to one side of the electrolyte sheet, and pressed at a pressure of 400 MPa for 10 min to form a sheet, and then carbon paper was added as a current collector to obtain a composite positive electrode sheet; Li-In alloy was added to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly, and then pressed at 50 MPa for 30 seconds to obtain the positive electrode material of the solid battery.

[0042] You can also use any one of the co-coated positive electrode materials prepared in Example 2 to Example 4 and grind it with the sulfide solid electrolyte LPSCl in a mass ratio of 7:3 to mix them evenly to obtain a composite positive electrode material; Then, 100 mg of LPSCl sulfide electrolyte was weighed and pressed at a pressure of 380 MPa for 1 min to form an electrolyte sheet, and then 10 mg of the obtained composite positive electrode material was added to one side of the electrolyte sheet, and pressed at a pressure of 400 MPa for 10 min to form a sheet, and carbon paper was removed and added as a current collector to obtain a composite positive electrode sheet; Li-In alloy was added to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly, and then pressed at 50 MPa for 30 seconds to obtain the positive electrode material of the solid battery.

[0043] Example 7 This embodiment provides a solid battery, in which the positive electrode material is prepared using the positive electrode material in Example 6, including the Li2ZrO3&ZrO2 co-coated positive electrode material described in any one of Examples 1-5.

[0044] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a Li2ZrO3&ZrO2 co-coated positive electrode material, characterized in that: The method comprises: The ZrO2 nanoparticles and the high nickel cathode material are first ball milled at a mass ratio of 0.1:100-10:100 to obtain a mixed material I; Adding the same molar amount of Li2ZrO3 as that of ZrO2 nanoparticles to the mixed material I, and performing a second ball milling to obtain the mixed material II; The mixed material II is subjected to high temperature annealing to obtain a Li2ZrO3&ZrO2 co-coated positive electrode material.

2. The preparation method according to claim 1, characterized in that: The first ball milling process specifically includes: first ball milling at 500 rpm for 1 minute, and then ball milling at 2000 rpm for 6 minutes; the second ball milling process specifically includes: first ball milling at 500 rpm for 1 minute, and then ball milling at 2000 rpm for 6 minutes.

3. The preparation method according to claim 1, characterized in that: The particle size of the ZrO2 nanoparticles is in the range of 2-100nm, and the particle size of the high-nickel positive electrode material is in the range of 100-5000um; the mass ratio of the ZrO2 nanoparticles to the high-nickel positive electrode material is 1:100-5:100; The high nickel positive electrode material is selected from any one of NCM523, NCM622, NCM811, Ni90 and NCA.

4. The preparation method according to claim 3, characterized in that: The particle size of the ZrO2 nanoparticles is in the range of 5-15nm, and the particle size of the high-nickel positive electrode material is in the range of 300-500nm.

5. The preparation method according to claim 1, characterized in that: The high temperature annealing of the mixed material II specifically includes: using an annealing temperature of 150-600° C. for a time of 1-24 hours.

6. The preparation method according to claim 5, characterized in that: The high temperature annealing of the mixed material II specifically includes: using an annealing temperature of 200-400° C. for 2-4 hours.

7. A method for preparing a solid battery positive electrode material, characterized in that: The following steps are involved: The Li2ZrO3&ZrO2 co-coated positive electrode material prepared by the preparation method according to any one of claims 1 to 6 and the sulfide solid electrolyte LPSCl are mixed and ground evenly to obtain a composite positive electrode material; The LPSCl sulfide electrolyte is pressed into an electrolyte sheet, and then the obtained composite positive electrode material is added to one side of the electrolyte sheet, pressed into a sheet, and carbon paper is added as a current collector to obtain a composite positive electrode sheet; A Li-In alloy is added to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly and pressing to obtain a positive electrode material.

8. The method for preparing a solid battery positive electrode material according to claim 7, characterized in that: When the Li2ZrO3&ZrO2 co-coated positive electrode material and the sulfide solid electrolyte LPSCl are mixed and ground, the mass ratio is 7:3; the mass ratio of the composite positive electrode material to the electrolyte sheet is 1:

10.

9. The method for preparing a solid battery positive electrode material according to claim 9, characterized in that: The LPSCl sulfide electrolyte is pressed into an electrolyte sheet, specifically comprising: 100 mg of the LPSCl sulfide electrolyte is pressed at 380 MPa for 1 minute to form a sheet; The obtained composite positive electrode material is added to one side of the electrolyte sheet and pressed into a sheet, specifically comprising: taking 10 mg of the composite positive electrode material and adding it to one side of the electrolyte sheet, and pressing it at a pressure of 400 MPa for 10 minutes; Adding Li-In alloy to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly and pressing, specifically comprising: adding Li-In alloy to the other side of the electrolyte sheet in the composite positive electrode sheet for assembly and pressing at a pressure of 50 MPa for 30 seconds.

10. A solid battery, comprising a positive electrode and a negative electrode, characterized in that: The positive electrode comprises a Li2ZrO3&ZrO2 co-coated positive electrode material prepared by the preparation method described in any one of claims 1-6.

Citation Information

Cited By

  • High-nickel positive electrode material for solid-state battery, preparation method of high-nickel positive electrode material and solid-state battery

    CN121726389A